Front Cover: Synthesis, Photophysics, Computational Approaches, and Biomolecule Interactive Studies of Metalloporphyrins Containing Pyrenyl Units: Influence of the Metal Center (Eur. J. Inorg. Chem. 12/2022). Issue 12 (5th April 2022) - Hahn da Silveira, Carolina; Chaves, Otávio A.; Marques, Amanda C.; Rosa, Nathália M. P.; Costa, Luiz Antônio S.; Almeida Iglesias, Bernardo
Abstract : The Front Cover shows the design of meso ‐tetra‐(1‐pyrenyl)porphyrin derivatives, which interact with biomolecules. These porphyrins were fully characterized by photophysical and theoretical methods. The presence of metal species in the porphyrin core influences the ground and excited states. Biomolecule interaction experiments show that these porphyrins interact spontaneously in the minor groove of CT‐DNA and in subdomain IB in the BSA pocket. The interaction depends on the nature of the metal ion. The cover was designed by Júlio A. F. Arvellos (scientific designer). More information can be found in the Research Article by B. Almeida Iglesias and co‐workers .